SOSIALISASI PENGOLAHAN DAN PEMASARAN PRODUK BABY NILA CRISPY DI DESA BUNKATE, KECAMATAN JONGGAT, KABUPATEN LOMBOK TENGAH - Syamsi, Hans Riadhi; Sarkawi; Maulana, Radifan Akbar Thirafi; Putri, Baiq Dewi Alya Nilyana; Ulfa, Siti Maria; Fadhilah, Afni Rifdah; Rohadi, Akbar Fitra; Ratila, Lalu Alfitra; Mawaddah, Usratul; Patmida, Baiq Naning Dwi (Jurnal Wicara, 2024)
Bunkate Village is a village located in Jonggat sub-district, Central Lombok Regency, West Nusa Tenggara Province. Bunkate Village consists of 6 hamlets. Based on the survey results, one of the potentials of Bunkate Village is the large number of people who are freshwater fish breeders, especially tilapia. This potential can be utilized into products that can improve the economy in Bunkate Village. Tilapia baby fish can be processed into food products in the form of snack products, namely crispy fish. The implementation methods include pre-activity, implementation of activities, evaluation of activities and product creation and marketing. Socialization and demonstration activities were carried out on Monday, January 22 2024 at the Bunkate Village Office Hall which was attended by Bunkate Village women. The organoleptic quality that crispy baby tilapia must produce is a golden brown color after frying. There is no fishy aroma in baby tilapia. The resulting taste is savory and salty. The texture of the baby tilapia produced is crunchy and crunchy. Promotion and marketing activities for processed baby tilapia products are carried out offline and online. Offline marketing is carried out by entrusting it to local kiosks in Bunkate Village. Meanwhile, online marketing is carried out through social media, namely Instagram and WhatsApp. It is hoped that this activity can help improve the village economy and advance MSMEs in Bunkate Village.